Influenza vaccine effectiveness against medically attended influenza illness in Beijing, China, 2014/15 season - Chunna Ma; Yang Pan; Li Zhang; Yi Zhang; Shuangsheng Wu; Ying Sun; Wei Duan; Man Zhang; Quanyi Wang; Peng Yang (Taylor & Francis Group, 2017)
Influenza vaccination is the most effective way of preventing influenza infections but its coverage is extremely low in China. Poor influenza vaccine effectiveness (VE) was reported in the 2014/15 season in some Northern Hemisphere countries with a predominance of H3N2 viruses belonging to the 3C.2a clade. However, there is limited information regarding the preventive effect of influenza vaccination for the same season in China, in which H3N2 viruses belonging to the 3C.3a clade predominated. Through influenza virological surveillance in Beijing, China during the 2014/15 season, we estimated the influenza VE against medically attended influenza-like illness (ILI) associated with laboratory-confirmed influenza virus infection using a test-negative design, and the effect of prior vaccination on current vaccination was examined. In total, 9297 patients with ILI were enrolled in this study. Among them, 3434 (36.9%) tested positive for influenza viruses: 2167 (63.1%) for A(H3N2), 1261 (36.7%) for influenza B, and 3 (0.1%) for A(H1N1)pdm09. The adjusted VE was estimated as −25% (95% CI: −70%, 8%) against A(H3N2) and −8% (95% CI: −50%, 23%) against B, with an overall VE of −18% (95% CI: −49%, 6%). The overall VE estimate for patients who received 2014/15 vaccination only was −12% (−57%, 20%), while VE for patients who received both 2013/14 and 2014/15 vaccinations was −27% (−72%, 7%). There was no evidence that the influenza vaccine protected vaccinees against medically attended influenza in Beijing, China during the 2014/15 season.